Efektivitas penggunaan media audio visual di SDN Wonosari 01 Kabupaten Bondowoso - Suwignyo Prayogo, Muhammad; Irma, Maghfirotul Firmaning Lestari (azkiya, 2022)
This study aims to discuss the Effectiveness of Using Audio Visual Media from Water Cycle Materials at SDN Wonosari 01 Kabupaten Bondowoso. This research method is a descriptive qualitative method with instrument literature studies, observations, and interviews in which the author collects information from various literature such as journals, books, and research journals, as well as observations of students and interviews with teachers. The results of the discussion obtained from this article are the success or failure of an education that is greatly influenced by its learning, including science learning which is a lesson that is often less attractive to students, with the exception of the Water Cycle material. This is because science has abstract concepts so of course it can make students difficult to understand it. Besides that, the era is growing rapidly so it takes a teacher of expertise to be able to make learning effective. Of course, regarding this, the teacher needs a learning media that can help him achieve a learning goal. In this study, the authors discuss the use of audio-visual media, the result of which is that students are enthusiastic about receiving learning so that learning objectives can be achieved.